Cerebrovascular adaptations to chronic hypoxia in the growth restricted lamb. Issue 45 (29th January 2015) - Castillo‐Melendez, Margie; Yawno, Tamara; Allison, Beth J.; Jenkin, Graham; Wallace, Euan M.; Miller, Suzanne L.
Abstract: Chronic moderate hypoxia induces angiogenic adaptation in the brain, reflecting a modulatory role for oxygen in determining cerebrovascular development. Chronic intrauterine fetal hypoxia, such as occurs in intrauterine growth restriction (IUGR) is likely to lead to a reduction in oxygen delivery to the brain and long‐term neurological abnormalities. Thus we investigated whether vascular remodeling and vascular abnormalities were evident in the brain of IUGR newborn lambs that were chronically hypoxic in utero. Single uterine artery ligation (SUAL) surgery was performed in fetuses at ∼105 days gestation (term ∼145 days) to induce placental insufficiency and IUGR. Ewes delivered naturally at term and lambs were euthanased 24 h later. IUGR brains ( n = 9) demonstrated a significant reduction in positive staining for the number of blood vessels (laminin immunohistochemistry) compared with control ( n = 8): from 1650 ± 284 to 416 ± 47 cells/mm 2 in subcortical white matter (SCWM) 1793 ± 298 to 385 ± 20 cells/mm 2 in periventricular white matter (PVWM), and 1717 ± 161 to 405 ± 84 cells/mm 2 in the subventricular zone (SVZ). The decrease in vascular density was associated with a significant decrease in VEGF immunoreactivity. The percentage of blood vessels exhibiting endothelial cell proliferation (Ki67 positive) varied regionally between 14 to 22% in white matter of control lambs, while only 1–3% of blood vessels in IUGR brains showed proliferation. A 66% reduction in pericyte coverage (α‐SMA and desmin) of blood vessels was observed in SCWM, 71% in PVWM, and 73% in SVZ of IUGR lambs, compared to controls. A reduction in peri‐vascular astrocytes (GFAP and laminin) was also observed throughout the white matter of IUGR lambs, and extravasation of albumin into the brain parenchyma was present, indicative of increased permeability of the blood brain barrier. Chronic hypoxia associated with IUGR results in a reduction in vascular density in the white matter of IUGR newborn brains. Vascular pericyte coverage and peri‐vascular astrocytes, both of which are essential for stabilisation of blood vessels and the maintenance of vascular permeability, were also decreased in the white matter of IUGR lambs. In turn, these vascular changes could lead to inadequate oxygen supply and contribute to under‐perfusion and increased vulnerability of white matter in IUGR infants.